Clinical implications of vitamin D deficiency - Matyjaszek-Matuszek, Beata; Lenart-Lipińska, Monika; Woźniakowska, Ewa (Menopause Review/Przegląd Menopauzalny, 2015)
Vitamin D deficiency is a common medical problem worldwide and its prevalence rises along with latitude, obesity, sedentary lifestyle, limited sunlight exposure and aging. A great body of evidence has shown that patients with vitamin D deficiency have increased cardiovascular risks and total mortality. Conversely, the presence of comorbidities progressive with age such as abdominal obesity, insulin resistance, type 2 diabetes and hypertension places the patients at an increased risk of vitamin D deficiency. The multidirectional effect of vitamin D deficiency is present in different phases of the aging process. Based on the literature review, the risk factors for vitamin D insufficiency most often found in post-menopausal women include limited sun exposure and time spent outdoors, inadequate dietary vitamin D intake, winter season and increased age. Vitamin D supplementation in this group might offer prevention of falls and fractures and may be beneficial for cardiovascular health, what may be especially important in osteoporotic and elderly populations. Prevention and treatment processes involve education regarding sunlight exposure and pharmacological cholecalciferol supplementation according to the recommendations for Central Europe. This manuscript reviews the role of vitamin D and its deficiency and considers their clinical implications, with particular regard to peri- and postmenopausal women.